Analysis of Potable Water Quality in Densely Populated Residential Environments (Case Study in Condongcatur Village) - Said, Ahmad; Suharno; Biyanti, Shupynur; Sapitri (Chemistry Department, Universitas Islam Indonesia, 2023)
Yogyakarta is a densely populated province in Indonesia. In order to maintain the comfort and health of the people of Yogyakarta, this study aims to analyze the quality of drinking water sources used by residents of Depok District with a population density of 3691.76 people/km2 in 2021, by taking water samples in Condongcatur Housing. The research was conducted by water intake survey method and testing experiments based on SNI No. 01-3554-2006 through test parameters of odor, taste, turbidity, pH, TDS, nitrite, nitrate, chloride, iron, and manganese levels. Based on the results of organoleptic and instrumental testing, the tested water samples were found to have met the quality standards set by PERMENKES RI No.492/MENKES/PER/IV/2010. Thus, the source of drinking water used by Condongcatur residents has met the required qualifications. This may be because local residents were able to maintain their water quality from human activities that can pollute the water quality. Nevertheless, water quality must always be maintained at all times considering the population in the area is increasing. Keywords: Water, drinkable water quality, populated residential environment